Trener sportowy dorosłych osób z niepełnosprawnością intelektualną jako ich przywódca w społeczeństwie1 - Świstek, Artur (Kultura-Społeczeństwo-Edukacja, 2021)
The article in a person representing the trait of an individual trait and a person of a sports trainer with intellectual disability and a personality traits leader with an intellectual personality and a personality traits leader with an intellectual personality.